Catalytic Alkylation Using a Cyclic S‐Adenosylmethionine Regeneration System. (7th February 2017) - Mordhorst, Silja; Siegrist, Jutta; Müller, Michael; Richter, Michael; Andexer, Jennifer N.
Abstract: S‐Adenosylmethionine‐dependent methyltransferases are versatile tools for the specific alkylation of many compounds, such as pharmaceuticals, but their biocatalytic application is severely limited owing to the lack of a cofactor regeneration system. We report a biomimetic, polyphosphate‐based, cyclic cascade for methyltransferases. In addition to the substrate to be methylated, only methionine and polyphosphate have to be added in stoichiometric amounts. The system acts catalytically with respect to the cofactor precursor adenosine in methylation and ethylation reactions of selected substrates, as shown by HPLC analysis. Furthermore, 1 H and 13 C NMR measurements were performed to unequivocally identify methionine as the methyl donor and to gain insight into the selectivity of the reactions. This system constitutes a vital stage in the development of economical and environmentally friendly applications of methyltransferases.